Heterosis, heterobeltiosis, dan aksi gen generasi F1 hasil persilangan kedelai (Glycine max (l.) Merrill) varietas Devon dan Dering - Dwi Sulastri; Florentina Kusmiyati; Karno Karno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2020)
ABSTRACT The objective of this research was to examine the value of heterosis, heterobeltiosis, and the degree of dominance of F1 generation as a result of crossing soybeans between Devon and Dering varieties. This research was conducted on January 2018 - April 2018 at the Plastic House of Randublatung District, Blora Regency and the Laboratory of Plant Breeding Physiology, Faculty of Animal Husbandry and Agriculture, Diponegoro University, Semarang. This study uses a experimental design single plant without replication with the randomization method Augmented design. As many as 16 seeds were planted from the Devon x Dering variety, 20 seeds from the Dering x Devon variety, 12 seeds from the Dering variety and 12 seeds from Devon varieties. The results showed that the heterosis and heterobeltiosis values were positive for Devon x Dering crossing occurred in all characters, while Devon x Dering crossing only occurred in the character of the number of seeds and the age of harvest. Positive dominant gene over action occurs in all the characters from Devon x Dering and the character of harvest age at the Dering x Devon crossing.Keywords: dominant, heterosis, heterobeltiosis, soybeans ABSTRAK Penelitian bertujuan untuk mengkaji nilai heterosis, heterobeltiosis, dan derajat dominansi generasi F1 hasil persilangan kedelai antara varietas Devon dengan Dering. Penelitian ini dilakukan pada tanggal Januari 2018 – April 2018 di Rumah Plastik Kecamatan Randublatung, Kabupaten Blora dan Laboratorium Fisiologi dan Pemuliaan Tanaman, Fakultas Peternakan dan Pertanian, Universitas Diponegoro, Semarang.Penelitianinimenggunakan rancangan percobaan single plant tanpa ulangan dengan metode pengacakan Augmented design. Kedelai yang ditanam sebanyak 16 benih hasil persilangan varietas Devon x Dering, 20 benih hasil persilangan varietas Dering x Devon, 12 benih varietas Dering dan 12 benih varietas Devon. Hasil penelitian menunjukkan bahwa nilai heterosis dan heterobeltiosis positif persilangan Devon x Dering terjadi pada semua karakter, sedangkan persilangan Dering x Devon hanya terjadi pada karakter jumlah biji dan umur panen. Aksi gen over dominan positif terjadi pada semua karakter hasil persilangan Devon x Dering dan karakter umur panen pada hasil persilangan Dering x Devon.Kata kunci: dominan, heterosis, heterobeltiosis, kedelai